Using WH-questions strategy and poetry to Improve writing skills among ESL Malaysian primary school learners during post-pandemic - Zachary Farouk Chai; Suyansah Swanto; Wardatul Akmam Din; Irma Wani Othman (Global Academic Excellence (M) Sdn Bhd, 2022)
The COVID-19 pandemic has shifted the teaching and learning of the English language from face-to-face interactions to remote teaching. In my context, most of my students did not engage with remote teaching during school closures due to certain factors such as lack of internet connection and the readiness of their parents. When schools reopened during the post-pandemic, I used the WH-questions strategy and poetry to improve my students' writing skills. WH-questions are considered guiding questions that can direct students to get new ideas in writing a text. Poetry is a form of literature that can help young learners tap into creativity by using words in writing. By using an action research design lens, this study aims to describe the process of using WH-questions strategy and poetry to improve writing skills among Year 5 primary school learners. The process consisted of four steps: planning, acting, observing and reflecting. Data were collected using a multimodal approach, including students' daily journals and structured-interview and the data gained were analysed narratively. Based on the data obtained, it was found out that the intervention used had successfully improved my learners' writing skills, especially in constructing correct simple sentences. I learned how to plan, conduct and evaluate WH-questions strategy as well as how to modify poetry writing to teach writing skills in English language lessons in the post-pandemic times.